Effects of brief psychoeducational program on stigma in Malaysian pre-clinical medical students: a randomized controlled trial - Fernandez, Aaron; Tan, Kit Aun; Knaak, Stephanie; Chew, Boon How; Shariff Ghazali, Sazlina (Springer, 2016)
Objective: If presented with serious mental illness (SMI), individuals’ low help-seeking behaviors and poor adherence to treatment are associated with negative stereotypes and attitudes of healthcare providers. In this study, we examined the effects of a brief psychoeducational program on reducing stigma in pre-clinical medical students. Methods: One hundred and two pre-clinical medical students (20–23 years old) were randomly assigned to face-to-face contact + educational lecture (n = 51) condition or video-based contact + educational lecture (n = 51) condition. Measures of pre-clinical medical students’ mental illness-related stigma using the Opening Minds Stigma Scale for Health Care Providers (OMS-HC) were administered at pre-, post-treatment, and 1-month follow-up. Results: A 2 (condition: face-to-face contact + educational lecture, video-based contact + educational lecture) by 3 (time: pre-treatment, post-treatment, and 1-month follow-up) mixed model MANOVA was conducted on the Attitudes, Disclosure and Help-Seeking, and Social Distance OMS-HC subscales. Participants’ scores on all subscales changed significantly across time, regardless of conditions. To determine how participants’ scores changed significantly over time on each subscale, Bonferroni follow-up comparisons were performed to access pairwise differences for the main effect of time. Specifically, pairwise comparisons produced a significant reduction in Social Distance subscale between pre-treatment and post-treatment and between pre-treatment and 1-month follow-up, and a significant increase between post-treatment and 1-month follow-up, regardless of conditions. With respect to the Attitudes and Disclosure and Help-Seeking subscales, pairwise comparisons produced a significant reduction in scores between pre-treatment and post-treatment and a significant increase between post-treatment and 1-month follow-up. Conclusions: Our findings provide additional evidence that educational lecture on mental illness, coupled with either face-to-face contact or video-based contact, is predictive of positive outcomes in anti-stigma programs targeting future healthcare providers.